Study of heat transfer characteristics of AL2O3 nanoparticles in heat pipes - Vivoganantha, Mukeshmahen (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The main objective of this project is to study thermal enhancement of the nanofluid and compared it with the base fluid. For this project, a test rig will be fabricated and the nanofluid will be prepared using aluminium oxide and water as the nanoparticle and base fluid respectively. Steps and processes regarding the fabrication of the test rig, preparation of nanofluid and the results from the experiment has been discussed in detail.